Educational research: issues and multidisciplinary nature. Theoretical and philosophical reflections - Valle, Ana María (Universidad Pedagógica y Tecnológica de Colombia, 2021)
It is a text that is the result of reflection, its main objective is to investigate the problems of educational research and its multidisciplinary nature. At first, it is assumed that: on the one hand, the problem of educational research is related to the conceptual and theoretical-methodological sense, which arises from thought and criticism of questions about education; on the other hand, the prefix "multi" not only refers to abundance and diversity, but rather refers to intersections, detours, eruptions and articulations of disciplines. In a second moment, educational research is reviewed from the disciplinarization of knowledge, as a combat between knowledge so typical of modernity. The theoretical-methodological approach that is followed is hermeneutics. It is considered that all interpretation has to protect itself against the arbitrariness of the occurrences and should rather orient its gaze to the "thing itself", which in this case this interpretive gaze is directed to the understanding of "the problems of educational research and its multidisciplinary character"